Effects of Short-Term Potassium Chloride Supplementation in Patients with CKD. Issue 9 (September 2022) - Gritter, Martin; Wouda, Rosa D.; Yeung, Stanley M.H.; Wieërs, Michiel L.A.; Geurts, Frank; de Ridder, Maria A.J.; Ramakers, Christian R.B.; Vogt, Liffert; de Borst, Martin H.; Rotmans, Joris I.; Hoorn, Ewout J.
Significance Statement: Observational studies show health benefits from a higher potassium intake, but it is unknown if this is tolerated by patients with CKD. This 2-week study indicates that 40 mmol/day potassium chloride supplementation (the estimated gap between actual and adequate intake) increased plasma potassium by 0.4 mmol/L in 191 patients with CKD (eGFR 31 ml/min per 1.73 m 2, 83% on renin-angiotensin inhibitors). The majority of patients (89%) remained normokalemic. Higher baseline plasma potassium and older age were risk factors for developing hyperkalemia after supplementation. Potassium chloride supplementation did not lower office BP, but did cause a tendency toward hyperchloremic metabolic acidosis. Longer-term studies should determine whether the cardiorenal benefits of adequate dietary potassium intake outweigh the risk of hyperkalemia in patients with CKD. Visual Abstract: Abstract : Background: Observational studies suggest that adequate dietary potassium intake (90–120 mmol/day) may be renoprotective, but the effects of increasing dietary potassium and the risk of hyperkalemia are unknown. Methods: This is a prespecified analysis of the run-in phase of a clinical trial in which 191 patients (age 68±11 years, 74% males, 86% European ancestry, eGFR 31±9 ml/min per 1.73 m 2, 83% renin-angiotensin system inhibitors, 38% diabetes) were treated with 40 mmol potassium chloride (KCl) per day for 2 weeks. Results: KCl supplementation significantly increased urinary potassium excretion (72±24 to 107±29 mmol/day), plasma potassium (4.3±0.5 to 4.7±0.6 mmol/L), and plasma aldosterone (281 [198–431] to 351 [241–494] ng/L), but had no significant effect on urinary sodium excretion, plasma renin, BP, eGFR, or albuminuria. Furthermore, KCl supplementation increased plasma chloride (104±3 to 105±4 mmol/L) and reduced plasma bicarbonate (24.5±3.4 to 23.7±3.5 mmol/L) and urine pH (all P <0.001), but did not change urinary ammonium excretion. In total, 21 participants (11%) developed hyperkalemia (plasma potassium 5.9±0.4 mmol/L). They were older and had higher baseline plasma potassium. Conclusions: In patients with CKD stage G3b–4, increasing dietary potassium intake to recommended levels with potassium chloride supplementation raises plasma potassium by 0.4 mmol/L. This may result in hyperkalemia in older patients or those with higher baseline plasma potassium. Longer-term studies should address whether cardiorenal protection outweighs the risk of hyperkalemia. Clinical trial number: NCT03253172